Phytochemical Analysis and Therapeutic Interests of Azadirchta Indica (Meliaceae) - Andrianarijaona Mamy; Ralaivaon-Dratsitonta Jumaël Edith Fabrice; Fatiany Pierre Ruphin; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
This study presents a phytochemical and structural investigation of Azadirachta indica, a plant widely used in traditional medicine in Madagascar for ailments such as malaria and fever. A systematic solid-liquid extraction of the plant's bark, employing solvents of increasing polarity, yielded various crude extracts. Subsequent phytochemical screening confirmed the abundance of key secondary metabolites, including alkaloids, tannins, polysaccharides, and saponins. The dichloromethane extract, having the highest yield, was selected for further analysis. A compound was successfully isolated from this extract using thin-layer chromatography (TLC) and preparative column chromatography. Its structure was then elucidated using a combination of one-dimensional spectroscopic techniques, including Electron Ionization Mass Spectrometry (EI-MS), 1H Nuclear Magnetic Resonance (NMR), and 13C NMR (with DEPT-135). The analysis of the spectral data, combined with a comprehensive literature review, led to the identification of the isolated molecule as 2-oxo-1,2-dihydroquinoline-4-carboxylic acid, an alkaloid with the molecular formula C10H7NO3. This compound is characterized by a two-ring system and six degrees of unsaturation, consistent with its spectral data. This research not only validates the traditional use of the plant but also provides a foundation for future pharmacological studies on this isolated compound.